COMPARATIVE CHATACTERISTICS OF DOMESTIC AND FOREIGN PRACTICES IN ESTAPLISING A UNIFIED MANAGEMENT STRUCTURE OF THE NATIONAL INTALLIGENT TRANSPORTATION SYSTEM - A. Merenkov (Вестник университета)
The article provides a comparative analysis of international practices in the implementation of a single control center of intelligent transportation systems in the case of Japan, the European Union and the United States of America. Conclusively proves the need of creation such a structure, considering options for its creation with respect to the prospect of realization in the Russian Federation. The article also examines the traffic management center as a pilot project to create a single control center intelligent transport systems in Russia.